Innovative Approaches to Learning and Islamic Education Methods - Muhammad Afif Ananta; Rahmat Pasaribu; Alwi Dahlan (Jurnal Pendidikan Islam, 2025)
This study discusses innovative learning approaches and Islamic education methods aimed at enhancing the quality of education and religious understanding among students. With the advancement of technology and changing social dynamics, conventional teaching methods often fall short of meeting modern educational needs. Therefore, innovative approaches are essential to integrate into the Islamic education system. This research explores various innovative methods, such as project-based learning, collaborative learning, and the use of digital technology in teaching. Additionally, it examines how the principles of Islamic education can be adapted and applied in the context of modern learning without compromising existing values ​​and traditions. The results of this study indicate that the integration of innovative approaches and Islamic education methods not only increases student motivation and engagement but also deepens their understanding of religious teachings. Thus, it is hoped that this research can serve as a reference for educators in developing more effective and relevant learning strategies to meet contemporary needs.